Detection of expanded-spectrum β-lactamases in Gram-negative bacteria in the 21st century. Issue 9 (September 2015) - Al-Bayssari, Charbel; Dabboussi, Fouad; Hamze, Monzer; Rolain, Jean-Marc
<x xml:space="preserve">Abstract</x> Emerging β-lactamase-producing-bacteria (ESBL, AmpC and carbapenemases) have become a serious problem in our community due to their startling spread worldwide and their ability to cause infections which are difficult to treat. Diagnosis of these β-lactamases is of clinical and epidemiological interest. Over the past 10 years, several methods have been developed aiming to rapidly detect these emerging enzymes, thus preventing their rapid spread. In this review, we describe the range of screening and detection methods (phenotypic, molecular and other) for detecting these β-lactamases but also whole genome sequencing as a tool for detecting the genes encoding these enzymes.